1999
DOI: 10.1006/dbio.1999.9435
|View full text |Cite
|
Sign up to set email alerts
|

Laminin and β1 Integrins Are Crucial for Normal Mammary Gland Development in the Mouse

Abstract: We have examined the role of integrin-extracellular matrix interactions in the morphogenesis of ductal structures in vivo using the developing mouse mammary gland as a model. At puberty, ductal growth from terminal end buds results in an arborescent network that eventually fills the gland, whereupon the buds shrink in size and become mitotically inactive. End buds are surrounded by a basement membrane, which we show contains laminin-1 and collagen IV. To address the role of cell-matrix interactions in gland de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 56 publications
5
91
0
Order By: Relevance
“…(c) Western blot analysis as in b, using recultivated tumor pieces from S35V12Ras (S35XT; isolated at weeks 11 and 16) and C40V12Ras (week 11) tumors. E-cadherin is lost in cell populations expressing high levels of S35V12 Ras protein, while cells expressing similarly high levels of C40V12Ras retain E-cadherin at normal levels signaling (Klinowska et al, 1999) are not properly formed, in contrast to organotypic structures in 3D cultures (S Gru¨nert, unpublished results).…”
Section: Discussionmentioning
confidence: 93%
“…(c) Western blot analysis as in b, using recultivated tumor pieces from S35V12Ras (S35XT; isolated at weeks 11 and 16) and C40V12Ras (week 11) tumors. E-cadherin is lost in cell populations expressing high levels of S35V12 Ras protein, while cells expressing similarly high levels of C40V12Ras retain E-cadherin at normal levels signaling (Klinowska et al, 1999) are not properly formed, in contrast to organotypic structures in 3D cultures (S Gru¨nert, unpublished results).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, it has been demonstrated that disruption of cell adhesion disturbs normal mammary gland morphogenesis, development, and differentiation (46). It has been proposed that an important role of maspin in mammary gland development is to regulate cell adhesion and motility, possibly by reducing the amount of ␤1-integrin at the cell surface (29); ␤1-integrin perturbation also alters the normal mammary gland development in the mouse (47,48). These results are in agreement with our observation that ␤1-integrin plays an important role in dome formation (4).…”
Section: Discussionmentioning
confidence: 99%
“…For collective migration in traction and collective migration ( Jacques et al 1998, Klinowska et al 1999, Grose et al 2002, Hegerfeldt et al 2002.…”
Section: Molecular Mechanisms Controlling Collective Migrationmentioning
confidence: 99%